Effects of the Healthy Start randomized intervention trial on physical activity among normal weight preschool children predisposed to overweight and obesity. - Mina Nicole Händel (PLoS ONE, 2017)
There is limited evidence to support the effectiveness of primary interventions aiming to prevent excess weight gain among young children. Evaluating behavioral changes, such as physical activity (PA), may add to future development of efficient interventions. The objective was to evaluate the effect on PA outcomes of the 15 month Healthy Start intervention that focused on changing diet, PA, sleep and stress management among normal weight but obesity-prone preschool children. Children were defined as obesity-prone if they had a birth weight > 4,000 g, mothers with a pre-pregnancy body mass index of > 28 kg/m2, or mothers with ≤ 10 years of schooling.From a baseline study population of 635 normal weight 2-6 year old preschool children from the greater Copenhagen area, parents of 307 children had given information on PA at both the baseline and follow-up examinations. PA was obtained from a 7 days recording in the Children's Physical Activity Questionnaire. Time used for sport activities were combined with outdoor playing time to achieve a proxy of total PA level of moderate to vigorous intensity.Linear regression analyses revealed that at follow-up the intervention group spent more time on sports and outdoor activities combined per week than the control group (ITT analyses: intervention: 400 min/week; 95% confidence interval (CI): 341, 459 versus control: 321 min/week; 95% CI: 277, 366; p = 0.02), although no significant intervention effects were seen for each of the subcategories, e.g. sports participation, outdoor activities, screen time, or commuting frequency.Our results suggest that the overall time spent on sports and outdoor activities combined was increased at follow-up among normal weight obesity-prone children, as a result of the Healthy Start intervention.ClinicalTrials.gov NCT01583335.